Strengthening care of injured children globally - Charles Mock; Francis Abantanga; Jacques Goosen; Manjul Joshipura; Catherine Juillard (The World Health Organization, 2009)
Part of the solution to the growing problem of child injury is to strengthen the care that injured children receive. This paper will point out the potential health gains to be made by doing this and will then review recent advances in the care of injured children in individual institutions and countries. It will discuss how these individual efforts have been aided by increased international attention to trauma care. Although there are no major, well-funded global programmes to improve trauma care, recent guidance documents developed by WHO and a broad network of collaborators have stimulated increased global attention to improving planning and resources for trauma care. This has in turn led to increased attention to strengthening trauma care capabilities in countries, including needs assessments and implementation of WHO recommendations in national policy. Most of these global efforts, however, have not yet specifically addressed children. Given the special needs of the injured child and the high burden of injury-related death and disability among children, clearly greater emphasis on childhood trauma care is needed. Trauma care needs assessments being conducted in a growing number of countries need to focus more on capabilities for care of injured children. Trauma care policy development needs to better encompass childhood trauma care. More broadly, the growing network of individuals and groups collaborating to strengthen trauma care globally needs to engage a broader range of stakeholders who will focus on and champion the improvement of care for injured children.